LITERACY SITUATION ANALYSIS OF AGRI POPULATION BETWEEN 1928 AND 2015 - Faruk KAYA (Fırat University, 2019)
A general definition of literacy is the ability of reading literatures of a language, perceiving and comprehending the materials which were read. According to the definition of UNESCO literacy is the ability to identify, understand, interpret, create, communicate and compute the written materials associated with varying contexts by using the records. Literacy is a phenomenon which allows i